2007
DOI: 10.1021/ja068079g
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Transistor Based on Individual Single-Crystalline Micrometer Wire of Perylo[1,12-b,c,d]thiophene

Abstract: Over the past 20 years, organic field-effect transistors (OFETs) based on soluble polymers and conjugated oligomers have attracted enormous interest for the realization of organic electronic devices. 1 Pentacene as the benchmark material with a mobility beyond 1.0 cm 2 V -1 s -1 has been reported. 2 Despite the great progress in the exploration of functional organic materials for OFETs, 3 fundamental aspects of carrier transport, especially the role of solid-state packing, still remain unclear. 4 From the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 29 publications
2
101
0
Order By: Relevance
“…Both diimides and perylenes are two families of compounds which are currently being studied due to their potential n-type semiconductor character and successfully been incorporated in the fabrication of electronic devices. [103][104][105][106] Absolute values for the electron-transfer rate constant and charge mobility were calculated through eqns. (1) and (8) and are shown in for series of cyanovinyl-substituted oligothiophenes using the MLJ model.…”
Section: Uv-vis Absorption Spectroscopy Uv-vis Spectra For Ph 2 Tz Amentioning
confidence: 99%
“…Both diimides and perylenes are two families of compounds which are currently being studied due to their potential n-type semiconductor character and successfully been incorporated in the fabrication of electronic devices. [103][104][105][106] Absolute values for the electron-transfer rate constant and charge mobility were calculated through eqns. (1) and (8) and are shown in for series of cyanovinyl-substituted oligothiophenes using the MLJ model.…”
Section: Uv-vis Absorption Spectroscopy Uv-vis Spectra For Ph 2 Tz Amentioning
confidence: 99%
“…[11][12][13][14][15] Fabrication of SCs or thin fi lms with small molecules is often carried out via high-cost gas-phase deposition due to low solubility; such fabrication methods would be diffi cult to scale up for practical applications. Small organic semiconducting molecules with enhanced solubility, which are readily processed, have been reported and have shown high-quality SC formation with excellent carrier mobilities ( μ = 0.1-6.0 cm 2 V − 1 s − 1 ) in fi eld-effect transistors (FETs).…”
Section: Highly Photosensitive J-aggregated Single-crystalline Organimentioning
confidence: 99%
“…Recently, we reported that the integration of S atoms into the perylene skeleton induces an extraordinary solid-state packing arrangement with the likelihood of double-channel superstructure, which is responsible for effective intermolecular hole transport. [8] In this contribution, we present our studies of a novel high performance organic semiconductor based on b-trithiophenes units, namely trans-1,2-(dithieno[2,3-b:3 0 ,2 0 -d]thiophene)ethene (1). To our surprise, the molecules adopt a compressed herringbone arrangement with marked multiple S. .…”
Section: Introductionmentioning
confidence: 99%